Immersive Media Presentation and Preschoolers’ Prosocial Behaviors: The Mediating Role of Theory of Mind - Chen, Ting; Jin, Chenglin (Frontiers in Psychology, 2022)
Although scholars have asserted that it is necessary to explore the effect of immersive media presentation on preschoolers’ prosocial behaviors, the empirical research, as well as the moderating roles of this link, remained limited. One hundred and twenty preschoolers (mean age = 5.4 years) were involved in three experiments of four waves. This study empirically examined the effect of media presentation, including immersive media presentation and traditional media presentation, on preschoolers’ prosocial behaviors and the moderating effect of theory of mind (ToM) on such links. After the experimental intervention, we find that the extent to which traditional media presentation and immersive media presentation impact preschoolers’ prosocial behaviors is different. First, the results show that preschoolers, who have been involved in traditional media presentation, do not notably reveal the development of their prosocial behaviors. However, in the group of high ToM, we find that traditional media presentation positively and significantly relates to preschoolers’ prosocial behaviors. That is to say, the positive influence of traditional media presentation depends on ToM. Second, the results also show that immersive media presentation positively and significantly relates to preschoolers’ prosocial behaviors whether ToM is high or not. Furthermore, ToM encourages the positive influence of immersive media presentation on preschoolers’ prosocial behaviors.